PENGOLAHAN LIMBAH LABORATORIUM KIMIA DENGAN SISTEM PENYARINGAN SEDERHANA - Fajri, Arinal; Arista, Dora; Sari, Maya (IAIN Batusangkar, 2018)
Increasing uses of chemicals in the laboratory result of waste substances increased. If those wastes are not carefully managed , various pollutions in the environment will occur. The research deals with the use of a simple filtering for laboratory type liquid waste before disposal. This study took the wastewater IAIN Batusangkar chemical laboratory as the object of research. The tools used to measure the concentration of waste are pH meters and TDS meters, with waste analysis before filtering are color: orange, temperature: 25.5°C, pH: 3.1, TDS (dissolved solids): 11.16, Salt (salinity level ): 8.38, COND: 16.78 mS and a waste volume of 300 ml filtered using simple tools and materials, tools with a height of 23 cm and supported with such materials as sponges, wood charcoal, sand, gravel, coconut fiber, cotton, small stone, with a height of each material in the tool that is 3.5 cm. The results shows that the simple filtering instrument for laboratory waste worked quite well, with a one-time analysis of waste where the results are as follow color: clear, temperature: 25.3°C, pH: 6.2, TDS: 13.23, SALD: 9.93, COND: 19.88 mS, volume of waste: 150 ml. It can be concluded that filtering is successfully filtered waste is approaching the normal pH of pure water that is 7.